STRUCTURE AND STYLE OF TRADITIONAL ENGLISH BALLADS - Eldorbek Erkin og’li Khamitov,; Turdimuratova Mexribanu Janabaevna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Traditional English ballads constitute a significant and long-standing genre of folk  literature  that  embodies  the  social  values,  historical  experiences,  and  cultural traditions of early English society. This research examines the structural patterns and stylistic  characteristics  that  define  traditional  English  ballads,  focusing  on  their narrative  organization,  poetic  framework,  and  expressive  techniques.  In  terms  of structure,  these  ballads  are  typically  composed  of  four-line  stanzas,  frequently following  alternating  iambic  tetrameter  and  iambic  trimeter,  along  with  consistent rhyme schemes such as ABAB or ABCB, which enhance rhythmic flow and support oral performance. Stylistically,  traditional  English  ballads  are  notable  for  their  clarity  and conciseness, prioritizing narrative progression over detailed description. The frequent use  of  dialogue  allows  the  storyline  to  unfold  dynamically,  engaging  the  audience while intensifying emotional impact. Repetition and refrains serve both mnemonic and artistic  purposes,  reinforcing  key  moments  and  aiding  memorization  in  oral transmission.  Additionally,  ballads  often  employ  formulaic  expressions,  symbolic elements, and narrative restraint, encouraging listeners to actively interpret the events rather than relying on explicit explanation. The  oral  and  anonymous  nature  of  traditional  English  ballads  has  played  a crucial role in shaping their stable yet flexible form. Although variations developed as the  ballads  were  transmitted  across  generations,  their  fundamental  structural  and stylistic features remained intact. This study demonstrates that the balance between formal  simplicity  and  narrative  effectiveness  enabled  traditional  English  ballads  to serve as both a form of popular entertainment and a vehicle for preserving collective cultural identity. Consequently, the enduring appeal of traditional English ballads lies in their well-defined structure and distinctive style, which continue to influence literary traditions.